The Role of Ethnic Identity, Perceived Cultural Distance and Social Network Composition in Predicting Acculturative Stress Among Indian International Students in the U.S - (:unkn) unknown (My University, 2020)
This study examined how ethnic identity, perceived cultural distance and cultural composition of social networks interacted to influence acculturative stress, among Indian international students studying in the United States. Acculturation models and the stress-buffering hypothesis served as theoretical frameworks. Participants consisted of 100 international students (56 % female, 44 % male; mean age = 24.72 years) who were mainly recruited with the support of Office of Student Affairs of a midwestern university. Data was collected through an online survey comprised of the Acculturative Stress Scale for International Students (ASSIS), Multigroup Measure of Ethnic Identity-R (MEIM-R), Cultural Distance Index (CDI) and a Cultural Composition of Social Network Scale. Results showed that ethnic identity, perceived cultural distance and cultural composition had significant main effects in predicting acculturative stress but only perceived cultural distance moderated the relationship between ethnic identity and acculturative stress. The findings of the current study may be useful in creating more outreach programs to this specific group of international students by better understanding their patterns of behavior. Keywords: acculturative stress, ethnic, identity, perceived cultural distance, cultural composition of social networks